Pedagogical Design Promoting Writing Productivity on the Doctoral Level – a Case Study from Finland - Lappalainen, Pia Helena (Journal of Academic Writing, 2016)
Publication productivity constitutes a key measure of institutional and researcher performance, determining success in university rankings and academic career development. To promote such productivity, Aalto University launched the Writing Doctoral Research course for engineers. To build a domain-specific course for doctoral candidates, their needs were examined quantitatively (n=325) and qualitatively (n=74). The aim was to identify pedagogy for raising the quality of publications and expediting doctoral degree completion. These investigations showed that 1) in the absence of sufficient supervision, engineers require more support in writing-related mental processes, 2) the mechanics of writing needs to promote argumentativity, 3) researchers lack precision when describing their research aims, 4) articulation of causality in data commentary requires more accuracy, and 5) instruments must be provided for writer self-correction. Instead of taking the lexicogrammar approach, the course was designed in a way that aligned with the principles of enculturation, assisting researchers in scientific positioning and socialization into their fields. Such an approach emphasizes reporting and structural conventions in engineering and the field-specific academic style.